A CLINICAL STUDY ON THE EFFICACY OF TRIPHALADI PRATISARANA IN KRUMIGRANTHI (BLEPHARITIS) - Ayanaraj, *P.; Mamatha, K. V.; K, Sujathamma (International Journal of Ayurveda and Pharma Research, 2015)
Blepharitis or inflammation of the eye lid is one of the most frequently encountered eyelid disorder. It is often a troublesome condition for patients owing to the long standing nature of disease and fluctuations in its severity. The chronic inflammation can cause the damage to occular surface ie to the conjunctiva and cornea because of the intimate relationship between the lids and ocular surface. Blepharitis, if not recognized and appropriately managed, can lead to worsening of signs and symptoms, changes in visual function, disrupted preocular tear film, structural changes in eyelash follicle resulting in trichiasis, madarosis, tylosis and a negative impact on quality of life of patients. Complete disease elimination is rarely achieved with the modern line of management which include topical antibiotic and weak steroid ointment. Based on the site of pathology, clinical features and the sequale of the disease it can be well correlated with the Sandhigata roga -Krumigranthi wherein the Krumis will later invade to the inner structures of eye. Pratisarana is one of the treatment modality explained for the treatment of Krumigranthi in the classics. Thus an observational study has been conducted on patients (n=10) of Shalakya tantra OPD of SKAMC, Bangalore to evaluate the efficacy of Triphaladi pratisarana in the management of Krumigranthi. The present study has come out with promising results in the reduction of signs and symptoms of anterior blepharitis. However clinical trials on large sample with long duration of follow up is necessary to establish the efficacy of Pratisarana as a procedure of choice and to analyse the recurrence rate after treatment.